(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2022)
Antibiotic resistance is a health problem experienced by living things, caused by long-term use of antibiotics. Thallasia hemprichii contains metabolites that have potential in the pharmaceutical field. Many studies show that seagrass has the activity of natural bioactive compounds as antifouling, antibacterial, and anti-fungal. The purpose of this study was to determine the number of isolates, morphological characteristics of endophytic fungi and to determine the antagonistic activity they produce against Staphylococcus aureus and Escherichia coli test bacteria. The study began on April-September 2021 using samples from the waters of Malang Rapat Village. The type of research conducted is descriptive. There were 4 stages of research, namely taking and preparation of roots and leaves of seagrass as hosts for endophytic fungi, isolation of endophytic fungi using direct planting method, observation of fungal morphology, and fungal antagonist test using the method of antagonist by fungi against test bacteria. The results obtained 3 isolates from root samples and 7 isolates from leaves, with isolates with septal hyphae belonging to D32.1, D32.2, A37, A35, A21, and D45. The characteristics of white pigmentation were obtained by isolates D32.2, D31, D21, D22, D18, and A37. Antagonism test against E. coli and S. aureus showed that isolate D18 had the largest diameter of the inhibition zone, which was 27.7 mm, and isolate D32.1 showed the smallest diameter of the inhibition zone, which was 13.1 mm against E. coli bacteria. D22 isolate against S. aureus bacteria showed an inhibition zone diameter of 5.9 mm.